An exploratory, cross-cultural study on perception of putative cyclical changes in facial fertility cues - Urszula M. Marcinkowska (Nature Portfolio, 2021)
Abstract Although many researchers have argued that facial traits evolved as honest cues to women’s current fertility (possibly via changes in facial femininity), evidence that women’s facial attractiveness is significantly, positively related to probability of conception throughout menstrual cycle is mixed. These mixed results could reflect differences among studies in the methods used to assess facial attractiveness (i.e., forced choice versus rating-scale methods), differences in how fertility was assessed, differences in perceiver characteristics (e.g., their own attractiveness), and facial preferences possibly being moderated by the characteristics of the living environment. Consequently, the current study investigated the putative effect of cyclical changes in fertility on women’s facial attractiveness and femininity (1) using forced choice and rating-scale method, (2) conducting both ovulation tests and repeated daily measures of estradiol assessing the conception probability, (3) based on a culturally diverse sample of perceivers, while (4) controlling for inter-individual variation. Although we found some limited evidence that women’s faces became more attractive when conception probability increased, these effects differed depending on the methods used to assess both attractiveness and fertility. Moreover, where statistically significant effects were observed, the effect sizes were extremely small. Similarly, there was little robust evidence that perceivers’ characteristics reliably predicted preferences for fertility cues. Collectively, these results suggest that mixed results in previous studies examining cyclical fluctuation in women’s facial attractiveness are unlikely to reflect inter-cultural differences and are more likely to reflect differences in the methods used to assess facial attractiveness and fertility.